Economic policy uncertainty and overinvestment: Evidence from Korea - Wenwen Jiang; Hwa-sung Kim (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2021)
The authors show that there is a negative relationship between economic policy uncertainty (EPU) and firm overinvestment using Korean data from 2007 to 2016. Since Jensen (1986) shows that a firm's free cash flow is an important factor of overinvestment, the authors examine how free cash flow influences the sensitivity of overinvestment to EPU. The authors find that a high level of free cash flow attenuates the negative effect of EPU on overinvestment. The authors find that there is no significant difference in the effect of EPU on overinvestment between Chaebol (Korean family-run conglomerates) and non-Chaebol firms, which is consistent with the literature that the features of Chaebol are weakening.
Keywords: D81; G18; G31; G41; 330; Economic policy uncertainty; Overinvestment; Free cash flow; Chaebol